KETEGARAN UPAH NOMINAL UNTUK TURUN: BUKTI EMPIRIS EKSPERIMEN - Joko Susanto; Yuni Siswanti; Windyastuti Windyastuti (KINERJA, 2014)
This study aims to analyze the downward nominal wage rigidity and the difference in degree of downwardÂ nominal wage rigidity between the economy with unemployment benefits and the economy without unemploymentbenefit. An experimental method in the form of nominal wage bargaining between employees and employersÂ was aplied in this study. The subject of the experiment are the alumni of UPN â€œVeteranâ€ Yogyakarta who havework experience at least 1 year. Panel data regression and t- test was employed to make conclusions fromÂ the experiment. Results show that there is evidence of downward nominal wage rigidity. Nominal wages in theeconomy with unemployment benefits was proved to be more rigid to decrease than the nominal wages in theÂ economy without unemployment benefit.